Digital Milton (Springer International Publishing, 2018)
Digital Milton is the first volume to investigate John Milton in terms of our digital present. It explores the digital environments Milton now inhabits as well as the diverse digital methods that inform how we read, teach, edit, and analyze his works. Some chapters use innovative techniques, such as processing metadata from vast archives of early modern prose, coding Milton's geographical references on maps, and visualizing debt networks from literature and from life. Other chapters discuss the technologies and platforms shaping how literature reaches us today, from audiobooks to eReaders, from the OED Online to Wikipedia, and from Twitter to YouTube. Digital Milton is the first say on a topic that will become ever more important to scholars, students, and teachers of early modern literature in the years to come.